2014
DOI: 10.5230/jgc.2014.14.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Morbidity in Elderly Gastric Cancer Patients Undergoing Gastrectomies

Abstract: PurposeThe prevalence of gastric cancer in the elderly is increasing. The purpose of this study was to clarify factors related to morbidity following gastric cancer surgery in elderly patients.Materials and MethodsFor this study, data from 411 patients who underwent curative gastrectomies with lymph node dissections between March 2010 and January 2013 were retrospectively studied using a prospectively designed database. Patients were divided into 2 groups (<70 years vs. ≥70 years). For each group, perioperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…However, most studies failed to address a good alternative for preoperative risk assessment by multivariable analysis of patient, tumour and treatment characteristics. In line with the present results, Shin and colleagues reported that older age (at least 70 years) and BMI were independent risk factors for the occurrence of complications. Here, BMI below 18·5 kg/m 2 was also an independent risk factor for complications in the entire cohort.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, most studies failed to address a good alternative for preoperative risk assessment by multivariable analysis of patient, tumour and treatment characteristics. In line with the present results, Shin and colleagues reported that older age (at least 70 years) and BMI were independent risk factors for the occurrence of complications. Here, BMI below 18·5 kg/m 2 was also an independent risk factor for complications in the entire cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The literature is ambiguous when it comes to the possible influence of co‐morbidities on postoperative outcomes. Some studies have suggested an independent effect of co‐morbidity on postoperative complications, but others did not find the number of co‐morbidities to influence postoperative outcome. In the present study, the absolute number of co‐morbidities did not affect postoperative outcome, but ASA grade had a strong influence on morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study [10] including a meta-analysis and a large randomized clinical trial showed that epidural analgesia leads to better analgesic efficacy and reduces the incidence of postoperative respiratory failure, especially in high-risk patients. Our study also revealed that EPCA had an analgesic effect superior to that of IVPCA in geriatric patients, who have increased perioperative risks after gastrectomy [11]. However, there were no differences between the two groups in the incidences of complications within the first 30 PODs, including cardiovascular complications, cerebrovascular accidents, wound problems, bile leakage, pulmonary complications, or delirium.…”
Section: Discussionmentioning
confidence: 46%